Control of Shoot Tip Necrosis in Shoot Cultures of Portulaca grandiflora Hook - Archana SRIVASTAVA; Aruna G. JOSHI (Notulae Scientia Biologicae, 2013)
Portulaca grandiflora, an important medicinal plant was found to show the incidence of shoot tip necrosis (STN) in shoot cultures obtained from nodal explants in Murashige and Skoog (MS) medium with 3% sucrose along with 8 µM Kinetin and 4 µM BAP. This physiological disorder is primarily due to the deficiency of calcium and boron content in the medium. Thus in the present work varying concentration of boron which was used in the form of boric acid (0.1-0.4 mM), calcium gluconate (3-30 mM) and calcium chloride (3-30 mM) were incorporated in MS medium and its effect on STN was evaluated. The observations revealed that 18 mM calcium chloride was the optimum concentration for lowering STN in shoot cultures to 40% after four weeks.